Cognitive Competence and Curriculum Development in Nurse Anesthesia Education: A Pilot Study - Swerdlow B; Osborne-Smith L; Arditti D; Hatfield LJ (Advances in Medical Education and Practice, 2023)
Barry Swerdlow,1 Lisa Osborne-Smith,1,2 Douglas Arditti,1,2 Lisa J Hatfield3 1Nurse Anesthesia Program, Oregon Health & Science University, Portland, OR, USA; 2Department of Anesthesiology and Perioperative Medicine, Oregon Health & Science University, Portland, OR, USA; 3Teaching and Learning Center, Oregon Health & Science University, Portland, OR, USACorrespondence: Barry Swerdlow, Oregon Health & Science University, SON 521, 3455 SW US Veterans Hospital Road, Portland, OR, 97239, USA, Tel +1 503 494 6468, Fax +1 503 346 8296, Email swerdlow@ohsu.eduBackground: Advanced practice nursing in the United States is shifting toward doctoral certification, most commonly a Doctor of Nursing Practice degree. However, there is limited evidence that this transition improves clinical competence.Purpose: The aim of this study was to determine whether modifications in a nurse anesthesia curriculum that transitioned from a Master of Nursing to a Doctor of Nursing Practice program were associated with improved cognitive performance using an oral examination.Design: A prospective, comparative observational study of students from a single, university-based nurse anesthesia program.Methods: This study was a small-scale investigation (n = 22) that used a quantitative method to compare the performances of consecutive cohorts of Master of Nursing and Doctor of Nursing Practice nurse anesthesia students as rated by oral examinations designed to evaluate critical thinking skills and previously shown to demonstrate internal consistency and reliability.Results: After completing an expanded curriculum, Doctor of Nursing Practice nurse anesthesia students performed significantly better than Master of Nursing students on oral examination, with improvements in cognitive domains previously identified as areas of underperformance by Master of Nursing students.Conclusion: Targeted curricular additions in a Doctor of Nursing Practice program correlated with improvements in nurse anesthesia student cognitive competence as measured by oral examination.Keywords: advanced practice nursing education, Doctor of Nursing Practice, graduate nursing education, nurse anesthesia, cognitive competence